Thoracic Spinal Anaesthesia for Modified Radical Mastectomy (MRM) - Derajad Bayu Atmawan; Hanifa Agung Kurniawan; Priyambada Priyambada (Journal of Anaesthesia and Pain, 2022)
Background: Breast cancer mostly affects patients older than 65 years old. Geriatric patients may have comorbidities so the selection of anaesthesia for breast cancer surgery is challenging. In the past decade, thoracic spinal anaesthesia as regional anaesthesia was feasibly performed for laparoscopic cholecystectomy and minor breast surgery. This article aims to evaluate thoracal spinal anaesthesia for Modified Radical Mastectomy (MRM) in our hospital settings.Case: Three cases of Thoracal Spinal Anaesthesia were carried out for MRM surgery after neoadjuvant chemotherapy treatment. This procedure consists of removal of breast tissue and the ipsilateral axillary contents. The comorbidities include hypertension, cardiomegaly, and mild anaemia. There was no conversion to general anaesthesia during surgery until completion. Duration for surgery less than 120 minutes.  No significant hemodynamic instability and complaint were found during intra and postoperative. Conclusion: From these cases, thoracal spinal anaesthesia was acceptable as regional anaesthesia for MRM in geriatric patient.